Clinical, environmental and histological distribution of BRAF, NRAS and TERT promoter mutations among patients with cutaneous melanoma: a retrospective study of 563 patients*. (1st March 2021) - Manrique‐Silva, E.; Rachakonda, S.; Millán‐Esteban, D.; García‐Casado, Z.; Requena, C.; Través, V.; Kumar, R.; Nagore, E.
Summary: Background: The distinct somatic mutations that define clinical and histopathological heterogeneity in cutaneous melanoma could be dependent on host susceptibility to exogenous factors like ultraviolet radiation. Objectives: Firstly, to characterize patients with cutaneous melanoma clinically and pathologically based on the mutational status of BRAF, NRAS and TERT promoter. Secondly, to elucidate the modified features due to the presence of TERT promoter mutations over the background of either BRAF or NRAS mutations. Methods: We performed a retrospective study on 563 patients with melanoma by investigating somatic mutations in BRAF, NRAS and TERT promoter. Results: We observed co‐occurrence of TERT promoter mutations with BRAF and NRAS mutations in 26.3% and 6.9% of melanomas, respectively. Multivariate analysis showed an independent association between BRAF mutations and a decreased presence of cutaneous lentigines at the melanoma site, and an increased association with the presence of any MC1R polymorphism. We also observed an independent association between TERT promoter mutations and increased tumour mitotic rate. Co‐occurrence of BRAF and TERT promoter mutations was independently associated with occurrence of primary tumours at usually sun‐exposed sites, lack of histological chronic sun damage in surrounding unaffected skin at the melanoma site, and increased tumour mitotic rate. Co‐occurrence of NRAS and TERT promoter mutations was independently associated with increased tumour mitotic rate. The presence of TERT promoter together with BRAF or NRAS mutations was associated with statistically significantly worse survival. Conclusions: The presence of TERT promoter mutations discriminates BRAF ‐ and NRAS ‐mutated tumours and indicates a higher involvement of ultraviolet‐induced damage and tumours with worse melanoma‐specific survival than those without any mutation. These observations refine classification of patients with melanoma based on mutational status.